Genetic Properties Responsible for the Transgressive Segregation of Days to Heading in Rice. Issue 5 (1st May 2019) - Koide, Yohei; Sakaguchi, Shuntaro; Uchiyama, Takashi; Ota, Yuya; Tezuka, Ayumi; Nagano, Atsushi J; Ishiguro, Seiya; Takamure, Itsuro; Kishima, Yuji
Abstract: Transgressive segregation produces hybrid progeny phenotypes that exceed the parental phenotypes. Unlike heterosis, extreme phenotypes caused by transgressive segregation are heritably stable. We examined transgressive phenotypes of flowering time in rice, and revealed transgressive segregation in F2 populations derived from a cross between parents with similar (proximal) days to heading (DTH). The DTH phenotypes of the A58 × Kitaake F2 progenies were frequently more extreme than those of either parent. These transgressive phenotypes were maintained in the F3 and F4 populations. Both A58 and Kitaake are japonica rice cultivars adapted to Hokkaido, Japan, which is a high-latitude region, and have a short DTH. Among the four known loci required for a short DTH, three loci had common alleles in A58 and Kitaake, implying there is a similar genetic basis for DTH between the two varieties. A genome-wide single nucleotide polymorphism (SNP) analysis based on the F4 population identified five new quantitative trait loci (QTL) associated with transgressive DTH phenotypes. Each of these QTL had different degrees of additive effects on DTH, and two QTL had an epistatic effect on each other. Thus, a genome-wide SNP analysis facilitated the detection of genetic loci associated with extreme DTH phenotypes, and revealed that the transgressive phenotypes were produced by exchanging the complementary alleles of a few minor QTL in the similar parental phenotypes.